Preparation and Characterization of Poly(3-hydroxybutyric acid)/Poly(vinyl acetate) Blend Films - Sharhan, Olla; Hamid Yahaya, Abdul; Mahmoud Nasef, Mohamed (Asian Journal of Chemistry, 2015)
Modification of poly(3-hydroxybutyric acid) (PHB) films by blending with poly(vinyl acetate) (PVAc) was investigated. The variation effect of poly(vinyl acetate) proportions in PHB/PVAc blend on the chemical structure, thermal stability, melting and phase morphology and crystallization behaviour were studied. The structure was characterized by Fourier transform infrared, thermogravimetric analysis, X-ray Diffraction (XRD) and field emission scanning electron microscopy. The properties of poly(3-hydroxybutyric acid) were found to be improved by blending with poly(vinyl acetate) and the level of improvement is a function of the proportion of poly(vinyl acetate) in the blend. The thermal stability for the blending was more stable than the pure polymers. The TGA results of the prepared polymers showed three-step decomposition assigned to the thermal degradation of poly(3-hydroxybutyric acid) hard and poly(vinyl acetate). For the XRD, the crystallization rate was decreased by blending poly(3-hydroxybutyric acid) with poly(vinyl acetate).